Organizing Sovereign Provinces in Independent America: The Republic of Córdoba, 1776–1827. Issue 2 (June 2014) - Verdo, Geneviève; Krieger, Angela
Abstract: This article considers the different political forms that emerged after the former viceroyalty of the Río de la Plata (which would eventually become Argentina) became independent. Based on the case of the Republic of Córdoba in the 1820s, it analyzes the territorial and institutional construction of an original political entity, the sovereign province. At the end of the eighteenth century, the reforms put in place under the Spanish Monarchy reinforced and politicized the territorial bodies that made up its empire, a process that continued after the revolution of independence. This created a tension between the sovereignty of these territorial bodies and the sovereignty of the "nation, " which operated according to different territorial constructions and brought different conceptions of sovereignty into play. While the Republic of Córdoba consolidated its internal sovereignty, it was also working toward integration into a larger political entity, envisaged as a confederation.